Time course effect of lipopolysaccharide on Toll-like receptors expression and steroidogenesis in the Chinese goose ovary. Issue 5 (May 2017) - Ying, ShiJia; Guo, JiaJia; Dai, ZiChun; Zhu, HuanXi; Yu, JianNing; Ma, WeiMing; Li, JiaYi; Akhtar, Muhammad Faheem; Shi, ZhenDan
Abstract : The ovary of Chinese goose is easily infected by microorganisms because of the mating behaviour in water, which causes decreased laying performance. This study investigated the time course effect of lipopolysaccharide (LPS) on the steroidogenesis and mRNA expression of Toll-like receptors ( TLR s), a class of key pattern recognition receptor, in the breeding goose ovary. The laying geese were treated intravenously with LPS for 0, 6, 12, 24 and 36 h, and all birds were slaughtered approximately 8 h after oviposition. The expression levels of TLR s in the white and yellowish follicles, and granulosa and theca layers of hierarchical follicles were examined by real-time PCR. All 10 members of avian TLR family were differentially expressed among the different follicular tissues. Moreover, at 24 and 36 h after LPS treatment, the hierarchical follicle morphological structure was altered, but the expression levels of TLR s were still higher than the control. Furthermore, during LPS treatment period, the expression pattern of TLR s 2A and 4 genes was similar to that of TLR15 in the white follicles, TLR s 1B, 5 and 15 in the yellowish follicles, TLR s 7 and 15 in the granulosa layer, and TLR s 1A, 2B, 3, 7 and 15 in the theca layer, which had a negative correlation with the kinetics of plasma P4 and E2 concentrations. In conclusion, the mechanism by which pathogen infection inhibited goose follicular growth and further decreased egg production may involve a gradually enhanced inflammatory response and reduced endocrine function. This may be due to stimulated TLR s in the ovary.